Retrenchment and restructuring in an age of austerity: what (if anything) can be learned from the affluent democracies? Retração e reestruturação em era de austeridade: será que se pode aprender alguma coisa com as democracias afluentes? - Paul Pierson (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
The article discusses some difficulties of drawing implications from welfare state reform in the Organisation for Economic Co-operation and Development for "middle-income countries", and whose welfare states have been less well institutionalized. It is argued that globalization's role in contemporary social policy dynamics were not unimportant, but social processes occurring within national contexts were probably more important. There is not a single "new politics of the welfare state" but distinct political dynamics in different "regimes" or "configurations", which are characterized by different problem loads and different structures of political opportunity. Different factors are crucial in explaining outcomes in different configurations and there is little reason to expect much convergence in social policy outcomes across regime type. Contemporary welfare state reform is depicted as a process of restructuring rather than dismantling, what can encourage the possibilities for developing coalitions advancing multi-dimensional agendas of welfare state reform. O artigo discute algumas dificuldades em fazer analogias entre as reformas do welfare state nos países da Organisation for Economic Co-operation and Development, para os "países de renda média", cujos sistemas de proteção social são menos institucionalizados. A globalização possui um papel na dinâmica da política social contemporânea, mas processos sociais ocorrendo dentro dos contextos nacionais foram provavelmente mais importantes para as configurações que a reforma assumiu. Não existe uma única "nova política do welfare state", mas distintas dinâmicas políticas em diferentes configurações ou "regimes", os quais se caracterizam por diferentes problemas e estruturas de oportunidades políticas. Diferentes fatores explicam os resultados em diferentes configurações, as quais tampouco produzem grande convergência quanto aos resultados de suas políticas sociais. A reforma atual do welfare state é pensada como um processo de reestruturação, e não de desmantelamento, o que encoraja a possibilidade de se pensar em coalizões para se estabelecer agendas multi-dimensionais de reformas de proteção social.